Chromatin Methylation Abnormalities in Autosomal Dominant Polycystic Kidney Disease - Xu, Jing; Xue, Cheng; Wang, Xiaodong; Zhang, Lei; Mei, Changlin; Mao, Zhiguo (Frontiers in Medicine, 2022)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease worldwide and is one of the major causes of end-stage renal disease. PKD1 and PKD2 are two genes that mainly contribute to the development and progression of ADPKD. The precise mechanism is not fully understood. In recent years, epigenetic modification has drawn increasing attention. Chromatin methylation is a very important category of PKD epigenetic changes and mostly involves DNA, histone, and RNA methylation. Genome hypomethylation and regional gene hypermethylation coexist in ADPKD. We found that the genomic DNA of ADPKD kidney tissues showed extensive demethylation by whole-genome bisulphite sequencing, while some regional DNA methylation from body fluids, such as blood and urine, can be used as diagnostic or prognostic biomarkers to predict PKD progression. Histone modifications construct the histone code mediated by histone methyltransferases and contribute to aberrant methylation changes in PKD. Considering the complexity of methylation abnormalities occurring in different regions and genes on the PKD epigenome, more specific therapy aiming to restore to the normal genome should lead to the development of epigenetic treatment.